Period Analysis and the Demand for Money - Kennedy, Charles (Review of Economic Studies, 1948)
Journal Article Period Analysis and the Demand for Money Get access Charles Kennedy Charles Kennedy Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 1, 1948, Pages 41–49, https://doi.org/10.2307/2296142 Published: 01 April 1948